2009
DOI: 10.1111/j.1538-7836.2008.03230.x
|View full text |Cite
|
Sign up to set email alerts
|

Dalteparin for the prevention of recurrence of placental-mediated complications of pregnancy in women without thrombophilia: a pilot randomized controlled trial

Abstract: Summary. Background: The role of anticoagulants for the prevention of placental-mediated pregnancy complications is uncertain. Objectives: Our aim was to investigate the effectiveness of dalteparin, a low-molecular-weight heparin, in preventing the recurrence of these complications in women without thrombophilia. Patients/methods: Between August 1 2000 and June 20 2007, 116 pregnant women with: (i) £ 16 weeksÕ gestation, (ii) no detectable thrombophilia, (iii) previous severe pre-eclampsia, newborn weight £ 5t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(104 citation statements)
references
References 35 publications
(43 reference statements)
4
94
0
6
Order By: Relevance
“…There was no statistical difference in the mean gestational age of delivery between the two groups in the present study (38.05 ± 2.02 vs. 37.58 ± 2.06 weeks). Similarly, Rey et al [8] in his study did not find any difference in gestational age between cases and controls. However, Mello et al [15] observed gestational age of delivery to be 37 weeks.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There was no statistical difference in the mean gestational age of delivery between the two groups in the present study (38.05 ± 2.02 vs. 37.58 ± 2.06 weeks). Similarly, Rey et al [8] in his study did not find any difference in gestational age between cases and controls. However, Mello et al [15] observed gestational age of delivery to be 37 weeks.…”
Section: Discussionmentioning
confidence: 56%
“…These complications occur due to placental vascular thrombosis which decreases placental perfusion [5][6][7]. Several studies have reported these placental-mediated complications even in patients without thrombophilia [8].…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular-weight heparin acts as an anticoagulant by inactivating thrombin and other proteases involved in hemostasis. An improvement in pregnancy outcome has been noted in women with a history of severe pre-eclampsia if low-molecular-weight heparin was administered [61]. However, so far, routine use of low-molecular-weight heparin as a preventive agent has not been implemented in clinical practice.…”
Section: Low-molecular-weight Heparinmentioning
confidence: 99%
“…Multiple clinical trials have reported that LMWH reduced the incidence of preeclampsia, as well as newborn weight < 5th percentile, FGR, major placental abruption or fetal loss after 20 weeks' gestation [20][21][22][23][24][25][26][27]; however, other trials of similar design have demonstrated no treatment effect with LMWH [28][29][30]. Most recently, the large, well-designed HEPEPE and EPPI trials reported that enoxaparin with ASA does not significantly reduce placental-mediated complications, including preeclampsia, when compared to aspirin alone [31,32].…”
Section: Lmwh For Preeclampsia Prevention: Evidence From Clinical Trialsmentioning
confidence: 99%